Tax Amnesty dalam Perspektif Good Governance - Happy Yustiari, Shinta (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
The national development aims for the prosperity of all the Indonesia’s people evenly and equitable needs large funding sourced from the major tax revenue. Tax Amnesty Policy is expected to be a driving force to taxpayer’s assets transferred into the country (repatriation) and the declaration of assets without transfer them into the country (declaration of foreign affairs). Implementation of Tax Amnesty in Indonesia is managed to become one of the most successful Tax Amnesty programs in the world. The level of public awareness and compliance with tax obligations during the Tax Amnesty period increased sharply, especially in getting taxes from the taxpayer’s assets abroad (both repatriation and declaration of foreign affairs). Tax Amnesty guarantees a more sustainable state budget. Tax Amnesty also ensures legal certainty in relation amongst the government, private sector, and society to be more transparent, accountable and participatory in an effort to sharpen the State's implementation of good governance.